KOMBINASI PENAKSIR RASIO-PRODUK EKSPONENSIAL UNTUK RATA-RATA POPULASI MENGGUNAKAN PROPORSI PADA SAMPLING GANDA - Nike Syelfina; Arisman Adnan; Sigit Sugiarto (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The estimators discussed in this paper are the exponential ratio estimator, the  exponential product estimator and the combination of exponential product and exponential ratio estimator on double sampling using proportion which is a review of the article written by Singh et. al. [Pakistan Journal of Statistics and Operations Research, 1(2): 18-32]. The three proposed estimators are biased. Hence, their mean square errors (MSE) are evaluated. Furthermore, the MSE are compared to obtain the most efficient one. Combination of exponential product and exponential ratio estimator on double sampling using proportion is the most efficient estimator among the other estimators.